2019
DOI: 10.1007/s40858-019-00291-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drought conditions on sweet orange (Citrus sinensis) plants infected with citrus tristeza virus (CTV)

Abstract: Brazil is one of the world's largest producers of citrus. However, production is challenged due to biotic and abiotic factors limiting crop health. The aim of this work was to evaluate the influence of water deficit in sweet orange (Citrus sinensis) cv. Pera Bianchi inoculated with citrus tristeza virus (CTV). Two isolates of CTV were used, one causing severe symptoms (Forte Rolândia) and the second causing mild symptoms (Pêra IAC), grafted on Rangpur lime (Citrus limonia) and Swingle citrumelo [Citrus paradis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
0
0
Order By: Relevance
“…It was suggested that the protection may be due to a virus-induced accumulation of osmoprotectants and antioxidants such as anthocyanins [41]. Likewise, proline, a proteinogenic amino acid acting on osmotic adjustment that helps subcellular structure stabilization and the elimination of free radicals, invariably had a higher concentration in sweet orange (Citrus sinensis) infected with citrus tristeza virus [43]. Survival of infected plants under extreme drought stress represents a conditional difference in fitness, assuming the surviving virus-infected plants can subsequently produce offspring.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the protection may be due to a virus-induced accumulation of osmoprotectants and antioxidants such as anthocyanins [41]. Likewise, proline, a proteinogenic amino acid acting on osmotic adjustment that helps subcellular structure stabilization and the elimination of free radicals, invariably had a higher concentration in sweet orange (Citrus sinensis) infected with citrus tristeza virus [43]. Survival of infected plants under extreme drought stress represents a conditional difference in fitness, assuming the surviving virus-infected plants can subsequently produce offspring.…”
Section: Discussionmentioning
confidence: 99%